2000
DOI: 10.1159/000054544
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin-Releasing Peptides Do Not Stimulate Prolactin Release in vivo

Abstract: The prolactin (PRL)-releasing activity of the novel prolactin-releasing peptides (PrRPs) was studied in vivo using male and lactating female rats. Whereas thyrotropin-releasing hormone effectively stimulated PRL and thyrotropin release as expected, PrRP in both animal models neither stimulated PRL secretion nor affected the release of other pituitary hormones. At the anterior pituitary level, in situ hybridization (ISH) histochemistry and Northern blot analysis revealed significantly higher expression levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 17 publications
2
46
1
Order By: Relevance
“…It is important to note that, in rats, doses of 50 and 500 nmol/kg in females and males respectively are required to stimulate plasma prolactin secretion and so it remains possible that similar dose rates on a per kg basis may affect prolactin secretion in sheep. However, in comparison, both in rats (Jarry et al 2000) and sheep (present study), low doses of TRH cause a marked stimulation of prolactin secretion, clearly indicating that PrRP has relatively low potency in both species. In the rat, GR3, the putative PrRP receptor, is abundantly expressed in the anterior pituitary gland (Welch et al 1995, Hinuma et al 1998, although more recent studies also show that receptor protein and mRNA are present at higher levels in the reticular thalamic nucleus and periventricular hypothalamus than in the anterior pituitary gland (Roland et al 1999).…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…It is important to note that, in rats, doses of 50 and 500 nmol/kg in females and males respectively are required to stimulate plasma prolactin secretion and so it remains possible that similar dose rates on a per kg basis may affect prolactin secretion in sheep. However, in comparison, both in rats (Jarry et al 2000) and sheep (present study), low doses of TRH cause a marked stimulation of prolactin secretion, clearly indicating that PrRP has relatively low potency in both species. In the rat, GR3, the putative PrRP receptor, is abundantly expressed in the anterior pituitary gland (Welch et al 1995, Hinuma et al 1998, although more recent studies also show that receptor protein and mRNA are present at higher levels in the reticular thalamic nucleus and periventricular hypothalamus than in the anterior pituitary gland (Roland et al 1999).…”
Section: Discussioncontrasting
confidence: 42%
“…Given the history of the PRF field, it is not surprising that subsequent studies by these and other authors have not provided convincing evidence in support of this role. For example, both in vivo and in vitro, PrRP has low potency in terms of its ability to stimulate prolactin secretion (Samson et al 1998, Jarry et al 2000. Further, it is now known that the highest concentration of PrRP containing neurones is found in the brainstem (Minami et al 1999) and that only small numbers of PrRP-positive neurones occur in the caudal dorsomedial hypothalamus (Minami et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Other recent studies have also implicated PrRP in the estradiol-induced prolactin surge of the rat (Matsumoto et al 1999b, Hizume et al 2000. In contrast, PrRP administered in vivo had no effect on prolactin secretion in both the rat (Jarry et al 2000) and sheep (Curlewis et al 2002). Although an extensive network of PrRP immunoreactive fibers has been described in the rat brain (Matsumoto et al 1999b), PrRP fibers are not detected in the external zone of the median eminence (Maruyama et al 1999.…”
Section: Discussionmentioning
confidence: 95%
“…However, much controversy surrounds this peptide. Although some studies suggest that PrRP stimulates prolactin release during in vitro (Hinuma et al 1998, Samson et al 1998 and in vivo (Matsumoto et al 1999b) studies, other investigations have revealed little or no effect (Jarry et al 2000, Seal et al 2000, Curlewis et al 2002. Moreover, little or no immunoreactive PrRP has been detected in the external zone of the median eminence in the rat, suggesting that PrRP is not released into the hypophyseal portal system (Maruyama et al 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators, in turn, have no been able to confirm this effect on PRL release in the experiments both: in vivo -in male or female rats (Jarry et al, 2000;Seal et al, 2000) and in vitro -on cells collected from lactating and virgin females (Samson et al, 2000); only high concentration of PrRPs-31 was capable to increase PRL release from dispersed lactotrophs derived from virgin female rats (Samson et al, 1998).…”
Section: Factors Stimulating Prolactin Releasementioning
confidence: 96%